I الكفاءة التربوية لمعلمي اللغة العربية والمحاولة التي قام بها المعلمون لتحسين كفاءتهم: دراسة ميدانية في تانجرانج الجنوبية - M. Rohim; Jimi Harianto (Study Program of Arabic Language Education (PBA), 2026)
This study aims to analyse field conditions related to the level of teaching competence of Arabic language teachers. This study also aims to analyse the efforts of teachers to improve their ability to teach Arabic language materials in Islamic Secondary Schools (Madrasa) in South Tangerang City. The researchers used descriptive qualitative methods by collecting information directly in the field. The research location is 6 Madrasas out of 18 Madrasas in South Tangerang Region. Which consists of two public madrasas and four private madrasas. The researchers examined teachers who had succeeded in obtaining a teaching profession certificate from the Government, and teachers who had not yet received certification. Researchers observed the teaching process and interviewed the teachers under study. Among the results of this study, is that the pedagogic abilities of Arabic teachers still need to be improved and developed. And a competency development process should be carried out in terms of educational competencies that are directly related to the learning process, by attending trainings and exercises both inside and outside Madrasas. However, the guidance and development process has not been carried out by the Directors of Madrasas, meanwhile, it is very necessary for Madrasas to pay more attention to the development of Arabic language teacher competencies.